Intercultural Communicative Competence in Hybrid Classrooms: Identity Negotiation among Indonesian EFL Students - Anugerah Febrian Syam (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study aims to reposition ICC as a relational practice negotiated situationally through the lens of classroom ethnography. The research was conducted over one semester in a Public Speaking course at a private university, involving 16 sixth-semester students. Data were collected through audio-visual recordings of classes, chat transcripts, presentation slides, reflective notes, and in-depth semi-structured interviews. Analysis was conducted iteratively through open coding, thematic clustering, and identity-positioning-based reading. The results show that ICC manifests as fluctuating positioning, shaped by fluency performance, code-switching strategies, camera visibility management, and cross-channel participation. The hybrid classroom functions as a sociomaterial intercultural contact zone that mediates legitimacy, vulnerability, and identity negotiation. This study concludes that ICC is more appropriately understood as situated accomplishment (relational, embodied, and technologized) rather than as a stable competence.